An analysis of grade 6 English first additional language reading comprehension questions in CAPS-aligned examinations - Sibanda, Lucy (Journal of Research on English and Language Learning (J-REaLL), 2025)
Reading comprehension, a crucial skill for successful text interaction, remains a significant challenge for many South African learners, as evidenced by their persistent difficulties in answering comprehension questions. This struggle underscores the importance of examining how comprehension assessments are designed and implemented. The South African curriculum assessment policy statement (CAPS) mandates a variety of cognitive levels in reading tests, using Barrett’s taxonomy for question design. However, there is a lack of research examining whether the reading comprehension questions in grade 6 English first additional language (EFAL) exams align with the cognitive levels. The purpose of this study is to examine the alignment of grade 6 EFA reading comprehension questions with the cognitive levels. The study employs Barrett’s taxonomy framework to categorize and evaluate reading comprehension questions in grade 6 EFAL exams. The results show a striking imbalance between actual question distributions and CAPS benchmarks: lower-order questions dominated at 68.75% (Paper 1) and 63.16% (Paper 2), far exceeding the CAPS target of 40%, inferential questions reached only 25.00% (Paper 1) and 26.32% (Paper 2), falling short of the 40% requirement, higher-order questions were critically underrepresented at 0.00% (Paper 1) and 10.53% (Paper 2), versus the 20% benchmark. The study recommends a substantive rebalancing of examination questions to achieve the CAPS-mandated distribution of cognitive levels (40% lower-order, 40% inferential, 20% higher-order).